Static analyses of laminated rhombic conoids. Issue 4 (10th May 2019) - Chaubey, Abhay Kumar; Kumar, Ajay; Chakrabarti, Anupam
Abstract : Purpose: This paper aims to present a new mathematical model for laminated rhombic conoids with reasonable thickness and depth. The presented model does not require the shear correction factor, as transverse strain variation through the thickness was assumed as a parabolic function. The zero transverse shear stress provision at the bottom and the top of rhombic conoids was enforced in the model. The presented model implemented a C 0 finite element (FE) model, eliminating C 1 continuity requirement in the mathematical model. The proposed model was validated with analytical, experimental and other methods derived from the literature. Design/methodology/approach: A novel mathematical model for laminated composite skew conoidal shells has been proposed. Parabolic transverse shear strain deformation across thickness is considered. FE coding of the proposed novel mathematical model was done. Slope continuity requirement associated with present FE coding has been suitably avoided. No shear correction factor is required in the present formulation. Findings: This is the first attempt to study the bending response of laminated rhombic conoids with reasonable thickness and depth. After comparisons, the parametric study was performed by varying the skew angles, boundary conditions, thickness ratios and the minimum rise to maximum rise (hl/hh) ratio. Originality/value: The novelty of the presented model is reflected by the simultaneous addition of twist curvature in the strain field as well as the curvature in the displacement field allowing the accurate analysis of reasonably thick and deep laminated composite rhombic conoids. The behavior of conoids differs from that of usual shells such as cylindrical and spherical due to the conoid's inherent twist curvature with its complex geometry and different location of maximum deflection.